Generalized Limit Sets - Hameed Hamzah , Sattar (Al-Qadisiyah Journal of Pure Science, 2019)
The major object of this paper is to create a types of group spaces, specifically, generalized small group spaces and generalized dispersive group spaces and use generalized limit sets to characterize these spaces. Their definitions are given by depending on the definition of generalized thin sets which itself depend on the concept of generalized closed set. Also, we investigate further properties about generalized limit sets and explain the relationship among these group spaces and generalized limit sets.